Effect of resin cement elastic modulus on the biaxial flexural strength and structural reliability of an ultra-thin lithium disilicate glass–ceramic material - Reis, Ana Flávia Nunes [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Paradella, Thais Cachuté [UNESP]; da Silva de Assis, Rita Adriana Souza [UNESP]; Valandro, Luiz Felipe; de Melo, Renata Marques [UNESP] (Springer Nature, 2023)
Objectives: Photo- and dual-polymerized resin–based luting agent was evaluated for elastic moduli effects on ultra-thin lithium disilicate (LD) glass–ceramic strengthening, structural reliability, and stress distribution. Materials and methods: One hundred-sixty LD discs (IPS e.max CAD, Ivoclar/Vivadent) were produced in ultra-thin thicknesses (half with 0.3 mm and the other half with 0.5 mm). The ultra-thin ceramic disks were coated with two different cement types (Variolink Veneer — V and Panavia F 2.0 — P). Two positive control groups were tested following hydrofluoric (HF) acid etching (LDt3, LDt5) and two negative control groups were tested for untreated ceramic (LD 3, LD 5). Biaxial flexural strength (BFS), characteristic strength (σ0) and Weibull modulus (m) were the response variables (n = 20) at the ceramic/resin cement interface (z = 0). Finite element analysis (FEA) was used to calculate maximum principal stress. Data were analyzed using two-way ANOVA, and Tukey’s test. Scanning electron microscopy (SEM) was used to analyze the failed specimens using fractography and surface morphology. Results: The BFS of LD at either thickness was not affected by cement types, as also demonstrated by FEA. Structural reliability significantly improved in the positive control group (LDt5). Conclusion: The cementation of ultra-thin LD with a resin-cement of varying elastic moduli did not influence BFS. LD surface modification by HF acid-etching increased the reliability. Clinical relevance: Ultra-thin anterior veneer designs made from lithium disilicate have been widely proposed and the apparent success of LD ultra-thin veneers was not influenced by the cement choice in the current studies albeit the elastic moduli luting agents used were of similar values.
Keywords: Finite element analysis; Fractography, Flexural strength; Glass ceramics; Resin cement; Weibull analysis